Bilateral repetitive transcranial magnetic stimulation ameliorated sleep disorder and hypothalamic–pituitary–adrenal axis dysfunction in subjects with major depression - Chen, Xing; Jiang, Fei; Yang, Qun; Zhang, Peiyun; Zhu, Haijiao; Liu, Chao; Zhang, Tongtong; Li, Weijun; Xu, Jian; Shen, Hongmei (Frontiers in psychiatry, 2022)
In this study, we sought to explore the effectiveness of bilateral repetitive transcranial magnetic stimulation (rTMS) over the dorsolateral prefrontal cortex (DLPFC) on depressive symptoms and dysfunction of hypothalamic-pituitary-adrenal (HPA) axis in patients with major depressive disorder (MDD).ObjectiveIn this study, we sought to explore the effectiveness of bilateral repetitive transcranial magnetic stimulation (rTMS) over the dorsolateral prefrontal cortex (DLPFC) on depressive symptoms and dysfunction of hypothalamic-pituitary-adrenal (HPA) axis in patients with major depressive disorder (MDD).One hundred and thirty-six adults with MDD were administrated drugs combined with 3 weeks of active rTMS (n = 68) or sham (n = 68) treatment. The 17-item Hamilton Depression Rating Scale for Depression (HAMD-17) was to elevate depression severity at baseline and weeks 4. To test the influence of rTMS on the HPA axis, plasma adrenocorticotropic hormone (ACTH) and serum cortisol (COR) were detected in pre- and post-treatment.Materials and methodsOne hundred and thirty-six adults with MDD were administrated drugs combined with 3 weeks of active rTMS (n = 68) or sham (n = 68) treatment. The 17-item Hamilton Depression Rating Scale for Depression (HAMD-17) was to elevate depression severity at baseline and weeks 4. To test the influence of rTMS on the HPA axis, plasma adrenocorticotropic hormone (ACTH) and serum cortisol (COR) were detected in pre- and post-treatment.No statistical significance was found for the baseline of sociodemographic, characteristics of depression, and psychopharmaceutical dosages between sham and rTMS groups (p > 0.05). There was a significant difference in the HAMD-17 total score between the two groups at end of 4 weeks after treatment (p < 0.05). Compared to the sham group, the rTMS group demonstrated a more significant score reduction of HAMD-17 and sleep disorder factor (HAMD-SLD) including sleep onset latency, middle awakening, and early awakening items at end of 4-week after treatment (p < 0.05). Furthermore, total score reduction of HAMD-17 was correlated with a decrease in plasma ACTH, not in COR, by rTMS stimulation (p < 0.05).ResultsNo statistical significance was found for the baseline of sociodemographic, characteristics of depression, and psychopharmaceutical dosages between sham and rTMS groups (p > 0.05). There was a significant difference in the HAMD-17 total score between the two groups at end of 4 weeks after treatment (p < 0.05). Compared to the sham group, the rTMS group demonstrated a more significant score reduction of HAMD-17 and sleep disorder factor (HAMD-SLD) including sleep onset latency, middle awakening, and early awakening items at end of 4-week after treatment (p < 0.05). Furthermore, total score reduction of HAMD-17 was correlated with a decrease in plasma ACTH, not in COR, by rTMS stimulation (p < 0.05).Bilateral rTMS for 3 weeks palliated depression via improvement of sleep disorder, and plasma ACTH is a predictor for the efficacy of rTMS, especially in male patients with MDD.ConclusionBilateral rTMS for 3 weeks palliated depression via improvement of sleep disorder, and plasma ACTH is a predictor for the efficacy of rTMS, especially in male patients with MDD.